1999
DOI: 10.1097/00000374-199909000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Cyclic AMP-Responsive Element Binding Protein Gene Transcription Factor in Genetic Preference for Alcohol Drinking Behavior

Abstract: Because P and NP rats are genetically bred for high and low alcohol drinking behavior, respectively, these results suggest the possibility that decreased expression of CREB protein in the amygdala may be associated with the high alcohol drinking behavior of P rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The basal protein levels of PKA-Cα were similar in the amygdaloid structures of P and NP rats. We reported earlier that CRE-DNA binding was lower in the nuclear extracts of whole amygdala, but not in the cortex, striatum, or hippocampus, of P compared with NP rats (34). These results suggest that there are innately lower protein levels of CREB and p-CREB in the amygdaloid, but not in the NAc, structures of P rats compared with NP rats.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The basal protein levels of PKA-Cα were similar in the amygdaloid structures of P and NP rats. We reported earlier that CRE-DNA binding was lower in the nuclear extracts of whole amygdala, but not in the cortex, striatum, or hippocampus, of P compared with NP rats (34). These results suggest that there are innately lower protein levels of CREB and p-CREB in the amygdaloid, but not in the NAc, structures of P rats compared with NP rats.…”
Section: Discussionmentioning
confidence: 54%
“…More specifically, it has been found that CREB-haplodeficient mice have a higher preference to alcohol (31). Also, it was found that the expression and phosphorylation of CREB and cAMP-responsive element-DNA (CRE-DNA) binding are lower in the whole amygdala of P rats than NP rats (34). Neuropeptide Y (NPY) is one of several CREB-related target genes (27,31,35) and has been shown to play a role in anxiety and alcohol abuse (8,10,(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ethanol withdrawal after chronic ethanol exposure leads to significant reductions in CREB phosphorylation and NPY protein levels in various rat brain structures, and decreased CREB phosphorylation and NPY expression in the central amygdala (CeA) might be associated with anxietylike behaviors during ethanol withdrawal (Pandey et al, , 2003bZhang and Pandey, 2003). It has also been found that CREB expression and phosphorylation as well as NPY protein levels are lower in amygdaloid brain structures of alcoholpreferring (P) rats compared with alcohol-nonpreferring (NP) rats (Hwang et al, 1999;Pandey et al, 1999). Interestingly, P rats display more anxiety-like behaviors and have higher ethanol preference than NP rats Stewart et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, other findings indicate that C57BL/6J mice are not anxious, consume large amounts of ethanol, and have lower basal levels of CREB, p-CREB, and NPY in the NAc shell but not in the amygdaloid structures compared with DBA/2J mice (Podhorna and Brown, 2002;Belknap et al, 1993;Misra and Pandey, 2003). On the other hand, alcohol preferring (P) rats consume large amounts of alcohol, are highly anxious, and have lower levels of CREB, p-CREB, and NPY in the central and medial amygdaloid but not in the NAc structures compared to alcohol non-preferring (NP) rats (Stewart et al, 1993;Li et al, 1993;Pandey et al, 1999bPandey et al, , 2003bPandey et al, , 2005Hwang et al, 1999). Interestingly, when PKA and CREB are lower in both NAc and amygdala such as in PKA (RII-b subunit) mutant and CREB haplodeficient mice, these mice have higher alcohol preference and display higher baseline anxiety levels as compared with littermate wild-type mice (Fee et al, 2003;Thiele et al, 2000;Pandey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%